Increasing The Growth and Yield of Green Lettuce (Lactuca sativa L.) with Fish Waste Liquid Organic Fertilizer - Saiful Arifin; Rizka Dwi Pratiwi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of applying liquid organic fertilizer from fish waste to the growth and yield of green lettuce. The research was conducted in Modong, Tulangan District, from December to January 2023. This study used a single factor randomized block design (CRD), namely fish waste liquid organic fertilizer consisting of 7 treatments, namely 10 ml/l; 20ml/l; 30ml/l; 40ml/l; 50ml/l; 60ml/l; and 70 ml/l. The data obtained were processed using Analysis of Variance (ANOVA), if there were differences between treatments, the 5% tukey test would be continued. The variables observed were plant height, number of leaves, fresh weight, dry weight, root length, and harvest index. It can be concluded that the effect of applying fish waste liquid organic fertilizer to green lettuce plants had a significant effect on plant height parameters with the highest average yield in the 50 ml/l treatment of 20.73, the number of leaves with the highest average yield in the 50 ml/l treatment of 4.00, the wet weight with the highest average yield in the 50 ml/l treatment was 44.30 grams, the dry weight with the yield of 3.90 grams, the root length with the highest average yield in the treatment 50 ml/l was 11.33, and the harvest index with the highest average yield was in the 50 ml/l treatment of 0.94. The results showed that the optimal application of fish waste liquid organic fertilizer on the growth of green lettuce plants was at a concentration of 50 ml/l.